Asymmetric and zwitterionic Blatter diradicals. Issue 10 (21st February 2023) - Miao, Fang; Ji, Yu; Han, Bo; Quintero, Sergio Moles; Chen, Hanjiao; Xue, Guodong; Cai, Lulu; Casado, Juan; Zheng, Yonghao
Abstract : Asymmetric diradical molecular systems with different resonance mechanisms are largely unexplored. Two conjugated asymmetric diradicals with Blatter and phenoxyl moieties (pBP and mBP) have been synthesized and studied in depth. Abstract : Asymmetric diradical molecular systems with different resonance mechanisms are largely unexplored. Herein, two conjugated asymmetric diradicals with Blatter and phenoxyl moieties (pBP and mBP ) have been synthesized and studied in depth. A complete set of spectroscopic, X-ray crystallographic and magnetic techniques, together with quantum chemical calculations, have been used. The para -isomer (pBP ) bears diradical and zwitterionic resonant forms, the latter by a electron delocalization mechanism, which are synergistically integrated by a sequence of nitrogen, provided by the Blatter moiety imine and amine (of different acceptor nature). In the meta -isomer (mBP ), the zwitterionic form promoted in pBP by the lone-pair electron of the amine nitrogen is not available, yet it possesses a pseudo-hyperconjugation effect where the N lone pair mediates in a bonding coupling in a counter homolytic bond scission mechanism. Both electronic effects converge to promote medium diradical characters and narrow singlet–triplet gaps to the two electronic isomers. All these aspects delineate the subtle balance that shapes the electronic structure of open-shell molecules, which is even more challenging in the case of asymmetric systems, such as those described here with asymmetric phenoxyl–Blatter diradicals.